2020
DOI: 10.1111/nyas.14413
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cannabinoid CB1R–GPR55 heteromers in neuronal subtypes of the Macaca fascicularis striatum

Abstract: The cannabinoid CB1 receptor (CB1R) is the most abundant G protein–coupled receptor in the central nervous system, consistent with the important role of endocannabinoids as neuromodulators. Cannabinoids also modulate the function of G protein–coupled receptor 55 (GPR55), which forms heteroreceptor complexes with the CB1R in the striatum. The aim was to characterize cannabinoid CB1R–GPR55 heteromers (CB1R/GPR55Hets) in the basal ganglia input nuclei of nonhuman primates, Macaca fascicularis, both in projection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The above-commented study of identification of neurons expressing CB 1 -GPR55_Hets in the striatum of naïve animals also concluded that the heteromers are not only expressed on cell surface but in intracellular structures (Martínez-Pinilla et al 2020). In this regard, it has been reported that the CB 1 R may be present in mitochondria and may mediate regulation of mitochondrial function by cannabinoids (Bénard et al 2012;Hebert-Chatelain et al 2014;Melser et al 2017;Gutiérrez-Rodríguez et al 2018).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The above-commented study of identification of neurons expressing CB 1 -GPR55_Hets in the striatum of naïve animals also concluded that the heteromers are not only expressed on cell surface but in intracellular structures (Martínez-Pinilla et al 2020). In this regard, it has been reported that the CB 1 R may be present in mitochondria and may mediate regulation of mitochondrial function by cannabinoids (Bénard et al 2012;Hebert-Chatelain et al 2014;Melser et al 2017;Gutiérrez-Rodríguez et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Triple immunofluorescent stains identified heteromers in parvalbumin, calretinin and nitric oxide positive interneurons. In contrast, cholinergic interneurons lacked heteromer expression (Martínez-Pinilla et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…The CB 1 receptor (CB 1 R) is the most abundant G-protein-coupled receptor (GPCR) superfamily member in mammalian CNS, it is particularly abundant in the olfactory bulb, hippocampus, basal ganglia, and cerebellum [22][23][24]. Moderate/low levels of this receptor have been found in the cerebral cortex, amygdala, hypothalamus, some areas of the brainstem, and the spinal cord [22,25]. Regarding CB 2 receptor (CB 2 R) expression in the CNS, it is primarily identified in microglia but also in some neurons in diverse brain areas including the cerebral cortex, hippocampus, and globus pallidus [23,[26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding CB 2 receptor (CB 2 R) expression in the CNS, it is primarily identified in microglia but also in some neurons in diverse brain areas including the cerebral cortex, hippocampus, and globus pallidus [23,[26][27][28][29][30][31]. At the neuronal level, these two receptors are preferentially located in the plasma membrane of pre-and post-synaptic terminals, but they can appear in the soma and dendrites of glutamatergic and serotonergic neurons, as well as in GABAergic interneurons [25,29,32,33]. Cannabinoids, endogenous, natural, or synthetic, may limit excitotoxic damage and enhance synaptic plasticity via CB 1 R or may exert anti-inflammatory and immunomodulatory actions via CB 2 R [17,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation